Peningkatan Keterampilan Literasi Lisan Bahasa Inggris Guru-Guru Multilingual Melalui Pelatihan Daily English Conversation in Real Life - Fitriati, Sri Wuli; Farida, Alief Noor; Hapsari, Christianti Tri; Chairunnisa, Nadya Zulfa; Wijayatiningsih, Testiana Deni; Putra, Angga Pratama Armaddi; Setyo Jati, Kukuh (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
English language skills in bilingual schools are critical. Teachers must teach students and help them communicate orally and in writing. This phenomenon is also seen in SD Tahfizhul Quran As-Sukarti Salatiga. Teachers must have good English communication skills since the school cooperates with NGOs from abroad. Currently, the number of human resources proficient in English is limited because only two teachers are proficient, and the others are not. The ability of teachers who can speak English varies, with most non-English teachers wanting to learn but lacking the confidence to speak. Although the school holds English courses every day, the lack of teachers' ability to communicate actively is still an issue. Two main problems were found from observations and interviews: the communication skills needed to support the bilingual classroom program and the lack of communication training for teachers. To overcome the problems at SD Tahfizul Quran As-Sukarti Salatiga, the service team created a program to improve real-life daily English communication skills for teachers at the school. The methods used in this training are lecture and discussion, practice, and role-play. Based on observations and questionnaires distributed after the training activities, teachers gave positive responses. They said this English training activity is essential for teachers to improve their competence and confidence. They also hoped there would be a sustainable program such as training that focuses on adding listening, speaking, and vocabulary skills.